Virus economics: an American tragedy - Robert Guttmann (Revue de la Régulation)
The global pandemic forces every country in the world into a complex set of balancing acts between virus spread containment, public health capacity, macro-economic stabilization measures, and business survival amidst depressed levels of activity. Irrespective of how countries perform under these unprecedented conditions of “virus economics”, they face a “Great Interruption” which accelerates trends and causes ruptures to the point of deepening crisis conditions. Nowhere among the richer OECD countries is this crisis process of the pandemic playing out more dramatically than in the United States where the virus is causing particular havoc. Virus economics has proven an American tragedy. Using the analytical concepts and methodological tools of Regulation Theory, notably with regard to the varieties of capitalism and on the nature of structural crises, invites the conclusion that the pandemic has caused a crisis of the accumulation regime which may alter capitalism for the better in the direction of sustainable development goals.